Re-elevation to species level and redescription of Serranochromis jallae and Serranochromis robustus (Teleostei: Cichlidae) - Stauffer, Jay R. Jr.; Bills, Roger; Skelton, Paul H.; Weyl, Olaf L.f. (Zootaxa, 2020)
Serranochromis robustus robustus from Lake Malaŵi and Serranochromis robustus jallae from Zambia were compared using morphological data. We re-elevated S. robustus jallae to species based on the following. Serranochromis robustus generally has a longer lower jaw (50.7–59.6% HL) than S. jallae (49.2–52.7% HL). Serranochromis robustus is not as deep-bodied as S. jallae as evidenced by the distance between the posterior insertion of the dorsal fin and the posterior insertion of the anal fin (13.4–15.1% SL in S. robustus vs. 14.9–18.4% SL in S. jallae). Additionally, S. robustus has a narrower least caudal peduncle depth (10.9–12.8% SL) than S. jallae (11.3–14.2% SL); the least caudal peduncle depth of all S. robustus was less than 12.8% SL while, except for the smallest specimen of S. jallae (88.1 mm SL), the least caudal peduncle depth was greater than 13.2% SL. Adults in breeding color of Serranochromis robustus are blue/green laterally, while adults in breeding color of S. jallae are yellow/green laterally. The marginal bands on the dorsal and caudal fins of S. jallae are bright orange in specimens from the Okavango River system and creamy yellow in Upper Zambezi specimens. In S. robustus, there is a yellow marginal band on the dorsal fin.